Scaling Effects on the Electrochemical Stimulation Performance of Au, Pt, and PEDOT:PSS Electrocorticography Arrays. (28th August 2017) - Ganji, Mehran; Tanaka, Atsunori; Gilja, Vikash; Halgren, Eric; Dayeh, Shadi A.
Abstract: The efficacy of electrical brain stimulation in combatting neurodegenerative diseases and initiating function is expected to be significantly enhanced with the development of smaller scale microstimulation electrodes and refined stimulation protocols. These benefits cannot be realized without a thorough understanding of scaling effects on electrochemical charge injection characteristics. This study fabricates and characterizes the electrochemical stimulation capabilities of Au, Pt, poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS/Au), and PEDOT:PSS/Pt electrode arrays in the 20–2000 µm diameter range. This study observes substantial enhancement in charge injection capacity up to 9.5× for PEDOT:PSS microelectrodes compared to metal ones, and 88% lower required power for injecting the same charge density. These significant benefits are strongest for electrode diameters below 200 µm. Detailed quantitative analyses are provided, enabling optimization of charge injection capacity with potential bias and symmetric and asymmetric pulse width engineering for all diameters. These systematic analyses inform the optimal design for acute and potentially chronic implants in regards to safety and clinically effective stimulation protocols, ensure the longevity of the electrodes below critical electrochemical limits of stimulation, and demonstrate that the material choice and pulse design can lead to more energy efficiency stimulation protocols that are of critical importance for fully implanted devices. Abstract : This study investigates and optimizes the charge injection performance of metallic (Au and Pt) and organic (poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/Au and PEDOT:PSS/Pt) electrocorticography electrode materials and quantifies their performance as a function of the electrode diameter. PEDOT:PSS microelectrodes exhibit significant benefits in charge injection capacity and reduce required power consumption compared to metallic electrodes. The results can help establish safe and efficient clinically relevant stimulation protocols for these electrode materials.